Pathways to Onset of Harmful Sexual Behavior - McKibbin, Gemma (Victims & offenders, 2024)
To develop harmful sexual behavior (HSB) early intervention strategies it is essential to understand how children come to engage in HSB. Through the lens of a pathways theory, this paper reports a scoping review of the literature in answer to the research question: What are the pathways to HSB onset for children and young people? Eight bibliographic databases were searched over the time period January 2000 to May 2022 using the following terms (and derivatives): harmful sexual behavior AND children and young people AND pathways. Forty-three papers were included and 10 pathways to onset identified through synthesis: Child sexual abuse victimization; Physical and emotional abuse; Living with domestic and family violence; Disrupted attachments; Sexual arousal; “Antisociality;” Pornography use; Inadequate sexual boundaries; Sexual attraction to children; and Hypermasculinity. The pathways are discussed in terms of opportunities for early intervention.